Re-crear: centro de arte, cultura e innovación para la reconciliación social en los talleres ferroviarios de bello. (2023)
The railway industrial heritage has been threatened by the divided recognition of what national railway lines mean, the abandonment of workshops, warehouses and maintenance centers has meant the loss of architectural, historical and cultural values ​​typical of railway architecture, buildings that today they have been immersed in contexts with major social problems that accelerate their processes of deterioration.